2005
DOI: 10.1073/pnas.0409253102
|View full text |Cite
|
Sign up to set email alerts
|

Molecular analysis reveals tighter social regulation of immigration in patrilocal populations than in matrilocal populations

Abstract: Human social organization can deeply affect levels of genetic diversity. This fact implies that genetic information can be used to study social structures, which is the basis of ethnogenetics. Recently, methods have been developed to extract this information from genetic data gathered from subdivided populations that have gone through recent spatial expansions, which is typical of most human populations. Here, we perform a Bayesian analysis of mitochondrial and Y chromosome diversity in three matrilocal and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
103
2
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 103 publications
(118 citation statements)
references
References 42 publications
12
103
2
1
Order By: Relevance
“…Thus, previous studies that analysed only a portion of the mtDNA genome and failed to find a difference relating to matrilocality versus patrilocality may have lacked sufficient resolution. Overall, our results confirm the idea that cultural practices can influence genetic variation 34 , but also demonstrate that the expected influence of matrilocality and patrilocality on genetic diversity may not always hold; in particular, in the present case, matrilocality seems more tightly regulated than patrilocality, in contrast to previous results 4 .…”
Section: Discussioncontrasting
confidence: 57%
See 3 more Smart Citations
“…Thus, previous studies that analysed only a portion of the mtDNA genome and failed to find a difference relating to matrilocality versus patrilocality may have lacked sufficient resolution. Overall, our results confirm the idea that cultural practices can influence genetic variation 34 , but also demonstrate that the expected influence of matrilocality and patrilocality on genetic diversity may not always hold; in particular, in the present case, matrilocality seems more tightly regulated than patrilocality, in contrast to previous results 4 .…”
Section: Discussioncontrasting
confidence: 57%
“…These results are surprising, as other studies have shown that, in general, there is more structure within human populations for Y-chromosome diversity than for mtDNA, which is likely to reflect the high global prevalence of patrilocality 1,5 . Furthermore, patrilocal practises seem to be more tightly regulated than matrilocal practices 4 , resulting in a higher female than male migration rate 2,[26][27][28] . Perhaps matrilocality has been more tightly regulated in the Semende, and patrilocality less tightly regulated in the Besemah, than has been observed previously.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This was probably a result of a lack of appropriate data sets, lack of computational power, and lack of tools to automate ABC inference. Our team has applied these techniques in the context of human evolution and ethology (Fagundes et al 2007;Hamilton et al 2005b). Concerning the ethology application (Hamilton et al 2005b), we have analyzed patterns of mitochondrial and Y-chromosome diversity in three matrilocal and three patrilocal groups from northern Thailand to infer by means of ABC the number of males and females arriving each generation in these populations and to estimate the age of their range expansion.…”
Section: Approximate Bayesian Computationmentioning
confidence: 99%